Genotypic Strain Determination of Multi-Drug Resistance (MDR) and Extended Drug Resistance (XDR) in Acinetobacter Baumanii from Tertiary Care Hospitals in Lahore: Genotypic Strain Determination of MDR and XDR in Acinetobacter Baumanii - Sheikh, Maryam; Amjad, Qurat Ul Ain; Zahra, Seerat Fatima Tu; Khan, Jalees Khalid; Munir, Zahid (Pakistan Journal of Health Sciences, 2025)
Antibiotic resistance in Acinetobacter baumannii poses a major future challenge, with a sharp rise in drug-resistant infections significantly limiting treatment options. Objectives: To determine the frequency of multidrug-resistant (MDR) and extended drug-resistant (XDR) Acinetobacter baumanii and the frequency of blaOXA-23, blaOXA-24, blaOXA-51, and blaOXA-58 among all other resistance genes responsible for resistance in Acinetobacter baumanii. Methods: A descriptive cross-sectional study was conducted in the Department of Pathology, King Edward Medical University, Lahore. Specimens were collected from the (Neonatal ICU, ICU, CCU) of Mayo Hospital, Lahore, and were processed at the hospital laboratory. Acinetobacter baumannii was identified on CHROMagar based on colony morphology and growth conditions, confirmed by biochemical tests. Antimicrobial sensitivity was assessed using the disc diffusion method, and PCR was performed for genotypic identification, with primer details in the data collection procedure. Results: Out of 67 samples, 19 (23.36%) were positive for Acinetobacter baumannii. Among these, blaOXA-23 (57.89%) was the most common resistance gene, followed by blaOXA-51 (47.36%). All 19 had the OXA-58 strain. The isolates showed 100% resistance to Penicillin, Ceftazidime, Cefepime, Imipenem, Levofloxacin, Doxycycline, and Septran. The most effective antibiotics were Ampicillin + Sulbactam (42.11%) and Piperacillin + Tazobactam (26.32%). Conclusions: The frequency of Acinetobacter baumanii was 28.36%. according to the study results. Among these positive isolates, carbapenem-resistant genes blaOXA-23 (57.89%) and bla-OXA-58 (47.36%) were the most frequent drug-resistant genes which were isolated. Regarding antimicrobial susceptibility, very few drugs showed sensitivity for Acinetobacter baumanii, which poses a major challenge for clinicians.